Pengaruh Efikasi Diri dan Kreativitas Terhadap Kinerja Karyawan Bagian Pramuniaga di Metro Department Store Karawang - Mila Amalia Firdaus; Enjang Suherman; Flora Patricia Anggela (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The aim of the researcher in conducting research was to determine the influence of self-efficacy on employee performance, to determine the influence of creativity on employee performance and to determine the influence of self-efficacy and creativity on employee performance (sales assistant department) at Metro Department store Karawang. This research design uses quantitative methods, the sampling technique used is probability sampling. Testing was carried out through validity and reliability testing of 30 respondents from a total population of 100 sales assistant employees with a sampling technique of 80 people obtained through Slovin. The method used in this research uses multiple linear regression analysis which was tested using SPSS 26 software. The results of this research show that there is a significant and partially positive influence of self-efficacy on employee performance variables, there is a significant and partially positive influence of creativity on employee performance and there is Simultaneous significant and positive influence of self-efficacy and creativity on employee performance (sales assistant department) at Metro Department store Karawang.